Antimicrobial Resistance in Enterobacterales Bacilli Isolated from Bloodstream Infection in Surgical Patients of Polish Hospitals - M. Kłos; M. Pomorska-Wesołowska; D. Romaniszyn; J. Wójkowska-Mach; A. Chmielarczyk (International Journal of Microbiology)
Background and Aims. Bloodstream infections (BSIs) are one of the most frequently observed hospital-acquired infections (HAIs). We sought to describe the epidemiology and drug resistance secondary Enterobacterales BSIs in surgical patients and check for any correlation with the type of hospital ward. Materials and Methods. This multicenter (13 hospitals in southern Poland) laboratory-based retrospective study evaluated adults diagnosed with BSI secondary to surgical site infection (SSI) hospitalized in 2015–2018; 121 Enterobacterales strains were collected. The drug resistance was tested according to the EUCAST recommendations. Tests confirming the presence of extended-spectrum β-lactamases (ESBLs) and bla resistance genes were carried out. The occurrence of possible clonal epidemics among K. pneumoniae strains was examined. Results. The prevalence of Enterobacterales in secondary BSI was 12.1%; the most common strains were E. coli (n = 74, 61.2%) and Klebsiella spp. (n = 33, 27.2%). High resistance involved ampicillin and ampicillin/sulbactam (92, 8–100%), fluoroquinolones (48–73%), and most cephalosporins (29–50%). Carbapenems were the antimicrobials with the susceptibility at 98%. The prevalence of ESBL strains was 37.2% (n = 45). All the ESBL strains had blaCTX-M gene, 26.7% had the blaSHV gene, and 24.4% had blaTEM gene. The diversity of Klebsiella strains was relatively high. Only 4 strains belonged to one clone. Conclusions. What is particularly worrying is the high prevalence of Enterobacterales in BSI, as well as the high resistance to antimicrobial agents often used in the empirical therapy. To improve the effectiveness of empirical treatment in surgical departments, we need to know the epidemiology of both surgical site infection and BSI, secondary to SSI. We were surprised to note high heterogeneity among K. pneumoniae strains, which was different from our previous experience.